Effect of lumbar-pelvic control on functionality in children with spastic cerebral palsy - Ahmed Hussein, Zeinab; Mohammed Mousa, Nehad; Soliman Ali, Mostafa (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Lack of pelvic control is a common functional impairment in children with spastic cerebral palsy (CP), so pelvic stability may be critical to improve controlled movements and activities in these children. The aim of this randomized controlled trial was to evaluate the effect of physical therapy programs combined with pelvic control exercises on controlled hip, knee, and ankle movements and gross motor functions in children with spastic CP. Thirty-two children diagnosed with spastic cerebral palsy at levels II and III on the gross motor functional classification system participated in this study. They were randomly and equally divided by a computerized program into control and study groups. The control group (eight boys and eight girls) received the designed therapy program for one hour. The study group (four boys and twelve girls) received lumbar-pelvic control exercises for 20 minutes in addition to 40 minutes of a physical therapy program. The program for both groups was applied three times per week for twelve weeks. After twelve weeks of treatment, the controlled movement, functional ability plus a joint range of motion of the hip, knee, and ankle were assessed by selective motor control scale, Peabody scales, and Kinovia software program, respectively. All statistical measures were performed through the Statistical Package for Social Studies (SPSS) version 20 for windows (SPSS, Inc., Chicago, IL). The results of our study showed a statistically significant improvement in median selective motor control, the Z score of Peabody scale, and the mean angle of hip, knee, and ankle range of motion after the treatment program in the study group compared with the control group (p < 0.05). Lumbar-pelvic control exercises are useful in improving the controlled movement and functional abilities in children with spastic diplegia CP when combined with a physical therapy program.